Praktikalitas dan Efektivitas Media Pembelajaran Terintegrasi Markerless Augmented Reality pada Materi Larutan Penyangga terhadap Hasil Belajar Peserta Didik Fase F - Zahra, Farah Rakhimy Az; Guspatni, Guspatni; Yuhelman, Nofri (PAKAR Pendidikan, 2025)
This study aimed to develop and evaluate the practicality and effectiveness of a learning media integrated with markerless augmented reality for teaching buffer solution concepts to senior high school students (Phase F). The media was designed to support students in understanding abstract chemical concepts through interactive three-dimensional visualizations—encompassing macroscopic, submicroscopic, and symbolic representations—without the need for physical markers. The study employed an Educational Design Research (EDR) approach using the Plomp model and a pre-experimental one-group pretest-posttest design. The sample consisted of 31 eleventh-grade science students from a senior high school in Padang, Indonesia. Practicality was assessed through questionnaires administered to both teachers and students, while effectiveness was measured by analyzing students’ cognitive learning outcomes based on pretest and posttest scores. Results indicated that the media was considered practical, with an average score of 83.13% from students (categorized as practical) and 89.55% from teachers (categorized as highly practical). In terms of effectiveness, the media demonstrated a moderate impact, with an average N-Gain score of 0.61. Significant improvements were observed across all learning indicators—macroscopic, submicroscopic, and symbolic levels. In conclusion, this markerless augmented reality-based media is suitable as a chemistry learning aid, as it enhances students’ conceptual understanding. The integration of augmented reality technology offers a more immersive, engaging, and relevant learning experience for today’s digital-native learners.